2012
DOI: 10.1021/jf3036885
|View full text |Cite
|
Sign up to set email alerts
|

Potential Antagonistic Effects of Nine Natural Fatty Acids Against Meloidogyne incognita

Abstract: Fatty acids, the essential components of life, were widely present in various seed cakes, gutter oil, and other resources. The objective of this study was to evaluate the potential antagonistic effects of nine fatty acids (FAs) against Meloidogyne incognita (root-knot nematodes). The results showed that butyric, caprylic, capric, lauric, myristic, palmitic, and oleic acids significantly reduced M. incognita reproduction, whereas cucumber (Cucumus sativus) biomass was not adversely affected by the tested FAs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 27 publications
(50 reference statements)
4
22
0
Order By: Relevance
“…C. elegans rapidly avoids Streptomyces secretions, which include dodecanoic acid. Interestingly, dodecanoic acid itself has been shown to have nematicidal activity ( Tarjan and Cheo, 1956 ; Abdel-Rahman et al, 2008 ; Gu et al, 2005 ; Dong et al, 2014 ; Zhang et al, 2012 ). The SRB-6 GPCR is essential for the rapid avoidance of Streptomyces and dodecanoic acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. elegans rapidly avoids Streptomyces secretions, which include dodecanoic acid. Interestingly, dodecanoic acid itself has been shown to have nematicidal activity ( Tarjan and Cheo, 1956 ; Abdel-Rahman et al, 2008 ; Gu et al, 2005 ; Dong et al, 2014 ; Zhang et al, 2012 ). The SRB-6 GPCR is essential for the rapid avoidance of Streptomyces and dodecanoic acid.…”
Section: Discussionmentioning
confidence: 99%
“…However, high levels of decanoic acid are not secreted by Streptomyces . Decanoic acid has also been shown to have nematicidal properties ( Tarjan and Cheo, 1956 ; Abdel-Rahman et al, 2008 ; Zhang et al, 2012 ), and decanoic acid, dodecanoic acid, and fatty acids of similar lengths are present in many plant seeds ( Zhang et al, 2012 ), indicating that avoiding decanoic acid in the environment may also be important to nematodes, outside the context of bacterial avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical nematicides are used to control nematodes, but its continued use can reduce its efficiency, making nematodes resistant, in addition to negative impacts on the environment and society (Javed et al, 2008;Zhang et al, 2012). Therefore, there is an increasing demand for development of new natural nematicides, aiming a partial or total replacement of chemical nematicides (Aissani et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Saponins like solanigroside A and solanigroside B (Zhou et al, 2007) as well as oleanane-type triterpenoid saponins exhibit LC 50 values against M. incognita ranging from 70.1 to 94.7 μ g ml -1 after 48 h (Li et al, 2013); while a saponin based commercial nematicide from Quillaja saponaria has been registered for nematode control in Europe (Giannakou, 2011). 4-methylphenol is of significant in vitro activity against M. javanica (Yang et al, 2015) while Zhang and co-workers have demonstrated that fatty acids like caproic, caprylic, capric, lauric, myristic, and palmitic cause significantly high mortality to M. incognita J2 (Zhang et al, 2012). Tannic acid has been proven nematicidal as well (Hewlett et al, 1997).…”
mentioning
confidence: 99%
“…We previously found that soil incorporation of powdered plant materials had lower EC 50 values for nematicidal activity than the respective extracts (Ntalli et al, 2010. Farmers do in fact utilize complex materials like waste resources, oil seed cake, and gutter oil to help manage M. incognita (Zhang et al, 2012) and efficacy is the sum of activities of active(s) against various nematode growth stages (egg, J2, and female laying eggs). The efficacy of the botanical nematicidals along with their side effects on non-target organisms, easiness of preparation, and cost effectiveness contribute to their overall significancy (Ntalli and Caboni, 2017).…”
mentioning
confidence: 99%